Receptions of the Ancient Near East in popular culture and beyond - Verderame, L. (Lorenzo); Garcia-Ventura, Agnès (Lockwood Press, 2020)
"This book is an enthusiastic celebration of the ways in which popular culture has consumed aspects of the ancient Near East to construct new realities. The editors have brought together an impressive line-up of scholars-archaeologists, philologists, historians, and art historians-to reflect on how objects, ideas, and interpretations of the ancient Near East have been remembered, constructed, reimagined, mythologized, or indeed forgotten within our shared cultural memories. The exploration of cultural memories has revealed how they inform the values, structures, and daily life of societies over time. This is therefore not a collection of essays about the deep past but rather about the stories we tell ourselves about ourselves"--